Decay of accelerated protons and the existence of the Fulling-Davies-Unruh effect - Vanzella, D. A. T. [UNESP]; Matsas, G. E. A. [UNESP] (American Physical Society (APS), 2001)
A theoretic-oriented strategy was taken to address the weak decay of uniformly accelerated protons. The decay of uniformly accelerated p+'s was analyzed using standard quantum field theory (QFT). It was shown that the FDU effect is essential to reproduce the proper decay rate in the uniformly accelerated frame.
Keywords: Elementary particles; Fermi level; Hamiltonians; Integrodifferential equations; Perturbation techniques; Polarization; Quantum theory; Accelerated proton decay; Fulling-Davies-Unruh effect; Quantum field theory; Protons